Promuovere la pace attraverso lo sport: il caso delle calciatrici afgane - Romina Gurashi; Pina Sodano (SHARE Press, 2023)
Through a microsociological analysis, the present essay aims to address the issue of peace and the role of female sport in society. As we demonstrate, there is a strong correlation between the creation of conditions of peace and the practice of sport, as well as between the practice of sport and the involvement of political choices. In this context, sport - and more precisely football - is found to represent a tool for female empowerment in Afghanistan. Through sport and the use of the latest technologies (like WhatsApp, Telegram, Facebook etc.) these young women resist the dominant political force of the Talibans and give themselves an autonomous collective representation. However, despite their compliance with political and religious norms, and the use of appropriate clothing they had to flee their country and continue promoting peace and female empowerment from abroad.